Acceptance Test and Iron Content Test Churros Formulation of RALE Flour (Red Beans and Soybeans) as an Alternative Snack to Prevent Anemia for Teenage Girls - Ayunis Naba'ur Rhodiyah; Juliana Christyaningsih; Erlyna Jayeng Wijayanti; Ani Intiyati (Politeknik Kesehatan Kemenkes Surabaya, 2023)
Conditions in which the amount of hemoglobin in the blood is below normal limits is called anemia. Iron deficiency is one of the causes of anemia which is still common in pregnant women and adolescents. The aim of this study was to determine the acceptability and levels of iron in churros formulated by RALE (red bean and soybean flour) as a snack to prevent anemia for girls. The research method is an experiment on 3 formulations of adding many flours: red bean: soybean with the formulations CP 1 (85:5:10), CP 2 (75:10:15), and CK 3 (100:0:0), using organoleptic tests in the form of likes and dislikes for color, taste, aroma, texture which were presented to 25 panelists. Test for iron content using ICP-OES method for the best organoleptic formulation and test results (CK 3). The results showed the CP 1 formulation were the most preferred with an average score of 4.32 which was included in the like category. The conclusion of this study showed organoleptic properties, the formulation favored by the panelists was the CP 1 formulation with a ratio of flour: red bean flour: soybean flour of 85:5:10, having an iron content of 3.86 mg/100 grams churros.